Profile of patients with disabilities submitted to dental treatment under general anesthesia (Research, Society and Development, 2022)
This study aimed to identify the profile of patients undergoing dental treatment under general anesthesia in a reference dental center in Ceará. Documental investigation based on medical records of patients seen from December 2012 to December 2018. Data collection took place in February 2020 using a printed collection instrument to fill in data on the sociodemographic profile, waiting time, and procedures performed. Data were organized in electronic spreadsheets and analyzed using descriptive statistics. Most were male (60%), with a mean age of 25±9, coming from the capital (74%), and dependent on the caregiver (67%). The diseases that led to referral were mostly related to mental disability (23.5%). Surgical procedures were the most performed with an average of 6 per patient. The waiting time to obtain care under general anesthesia was 76 days, most of which did not need to return (89%) for other dental procedures. Knowledge of the profile directs managerial planning aimed at the multidisciplinary care demand of patients with disabilities who cannot obtain dental care under local anesthesia.